Students’ Responses to the Implementation of the Inquiry-Based Pictorial Riddle Method via Online in the Concept of Fluid Static - Syukri, Muhammad; Husna, Wardatul; Ngadimin, Ngadimin; Andriani, Ayu; Halim, Lilia (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2022)
The Covid-19 pandemic has led to the issuance of government policies that require distance learning. One approach so that students remain motivated to learn is to use a method that allows two-way interaction between teachers and students even though learning is online. The research was conducted in SMA Negeri 4 Vocational High School, class XI MIA 3, involving 34 students. The research method used was descriptive research which describes students’ responses to the implementation of the inquiry-based pictorial riddle method online. The data collection technique used four alternative answers. The research data was processed using the Likert scale. Based on the results of the study, students’ responses to the inquiry-based pictorial riddle method were very good. This is evidenced by the response from most students who feel interested and get many benefits when learning to use inquiry-based pictorial riddles during online learning.